Does social investment influence poverty and economic growth in South Africa: A cointegration analysis? - Ogujiuba Kanayo; Ntombifuthi Mngometulu (Economies, 2022)
Despite having a middle-income status, many South African households are either already in or are about to fall into poverty. The income and wealth distribution in South Africa is among the most uneven in the world, and many households lack even the most basic access to healthcare, clean energy, and clean water. Although it has increased government spending, South Africa's government has made significant steps to combat poverty and inequality and encourage economic growth. Understanding the connection between social investment, poverty, inequality, and economic growth is, therefore, necessary to comprehend the ambiguity that currently prevails. In order to analyze the effects of social investment on poverty and economic growth in South Africa between 1990 and 2020, this paper uses the cointegration technique. The cointegration estimates indicate that there is no correlation between social investment, poverty, inequality, and economic development. According to study findings, South Africa's macroeconomic policies, which seem to be more urban-focused, need to be modified and redirected into inclusive policies with strict constraints to assure their implementation. The transformation of rural and township life will be aided by this plan.
Keywords: 330; inequality; government; growth; poverty